Первоклассница: повесть / Е. Л. Шварц ; худ. Е. Володькина - Шварц Евгений Львович (Детвора, 2011)
Экземпляры: ДБ (20120830) / Инвентарный номер: 41049zzzzz / Цена: 183.38 / Сис.шифр: 84(2) / Авт.знак: Ш 33 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)